Influence of draw frame passages on fibre orientation in sliver and air vortex spun yarn quality (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
This study examines the impact of the Integrated Draw Frame (IDF) process, a method gaining popularity in recent years, on fibre orientation and yarn quality of air vortex spun yarns compared to the conventional Non-Integrated Draw Frame (Non-IDF) process. The effects of IDF and Non-IDF passages on sliver orientation parameters, such as cutting ratio, combing ratio and extended fibre percentage, are evaluated in both carding and finisher draw frame slivers. Yarns produced through the Non-IDF route exhibit higher yarn strength and elongation, complemented by better fibre alignment, lower unevenness percentages and fewer imperfections compared to those produced via the IDF process. Similarly, slivers from the Non-IDF process demonstrate superior cutting ratio, combing ratio and extended fibre percentage compared to slivers from the IDF route. This improvement is attributed to the additional doubling and drafting processes employed in the Non-IDF method, which result in more parallelised, straightened and oriented fibres. Although the yarn quality in the IDF process is slightly lower than that of the Non-IDF process, the manufacturing cost is reduced by Rs. 1.17/Kg in the IDF process.